SPECIFICS OF MOTIVATIONAL-SEMANTIC SPHERE OF MODERN TEACHERS - A. M. Luzhetskaya (Acta Biomedica Scientifica, 2015)
The article is concerned with the role of teacher's motivational-semantic sphere in his or her professional activity. The motivational-semantic spheres structure comprising dynamic and semantic component is described on the basis of motivation and semantic approach. Dynamic component is represented by motivation formation relevant activity (i.e. motivations). Semantic component is represented by lasting and abstract cognitive and rational structures and leads to personality meaning-making. Results of empirical study of teacher's motivational-semantic sphere at different levels of professionalization (adapter-teacher, internal, expert, authority, mentor) according to E.A. Klimov are given. The analysis of the general and specific characteristics of each stage of professionalization is performed. Differences (divergent features) and general properties (invariant) of teachers appear in manifestation parameters and in the structure of motivational-semantic sphere. The limitations, - qualities do not meet the requirements of the profession, and resources motivational-semantic sphere of teachers are revealed. The structure of motivational-semantic sphere of the modern teacher is obtained, based on factorization of the empirical research's results.